FRI0754-HPR Impact of corticosteroid utilization on biologic disease-modifying antirheumatic drug initiation among patients with rheumatoid arthritis. (15th June 2017) - Spivey, CA; Griffith, J; Kaplan, C; Postlethwaite, A; Ganguli, A; Wang, J
Abstract : Background: Treatment guidelines recommend low dose corticosteroids (steroids) as an effective short-term (<3 months) therapy among rheumatoid arthritis (RA) patients to "bridge" patients until benefits of disease modifying anti-rheumatic drugs (DMARDs) are observed and in flare management. 1 Physician quality reporting system (PQRS) measures in the US require a documented management plan for patients on steroids >10 mg/day and this may be a prompt to advance RA therapy. Understanding steroid treatment patterns and associated burden prior to biologic DMARD initiation can inform clinical and policy decision-makers on the appropriate use of these two drug classes in RA management. Objectives: To examine effects of steroid treatment patterns on initiation of biologic DMARDs and adverse effects of steroid utilization before biologic DMARD initiation among patients with RA. Methods: A retrospective analysis was conducted of adult RA patients (18 and older) in the US MarketScan Database (2011- 2015). The earliest date a patient was diagnosed with RA was the index date. The following patterns of oral and injectable steroid utilization were analyzed: whether steroids were used; duration of steroid use (short/long duration defined as < or ≥3 months); and steroid dosage (low as <2.5 mg/day, medium as 2.5-<7.5 and high as ≥7.5 mg/day). Kaplan-Meier survival analysis was used to compare time to initiation of first biologic DMARD across groups of steroid utilization. The effects of steroid use on initiation of biologic DMARDs were examined using Cox proportional hazards models. Likelihood and number of adverse events were examined using logistic and negative binomial regression models. Independent variables in all models included patient demographics and health characteristics. Results: A total of 25, 537 patients were included (40.82% used steroids). Based on Kaplan-Meier survival analysis, steroid users (Figure 1 ), those with longer duration, and in lower dosage categories had delayed time to initiation of a biologic DMARD than their counterparts (nonusers, those with shorter duration and higher dosages, respectively) (P<0.001). According to Cox proportional hazards model, lower hazard of biologic DMARD initiation was associated with steroid use ([HR]=0.89, 95% Confidence Interval [CI]=0.83–0.96, compared to nonusers), longer steroid duration (HR=0.73, 95% CI=0.60–0.89 compared to short duration) and lower dosages (HR=1.10, 95% CI=0.99–1.23 for medium dose and HR=1.93, 95% CI=1.59–2.34 for high dose compared to low dose). Higher likelihood of adverse events was associated with steroid use (Odds Ratio [OR]=1.13, 95% CI=1.06–1.20), and longer duration (OR=1.75, 95% CI=1.47–2.09) than their counterparts. Likelihood of adverse events did not significantly differ across dosages. Similar effects of steroid utilization were found on the number of adverse events. Conclusions: The findings indicate that RA patients who use steroids, those with longer duration and lower dosages have delayed initiation of biologic DMARDS than their counterparts. RA patients who use steroids and those with longer duration have higher likelihood/number of adverse events prior to initiating biologic DMARDS. References: Singh JA, et al. doi: 10.1002/acr.22783. Disclosure of Interest: C. Spivey Grant/research support from: AbbVie, J. Griffith Shareholder of: AbbVie, Employee of: AbbVie, C. Kaplan Grant/research support from: AbbVie, A. Postlethwaite Grant/research support from: AbbVie, A. Ganguli Shareholder of: AbbVie, Employee of: AbbVie, J. Wang Grant/research support from: AbbVie